AN ANALYSIS OF THE STUDENTS’ SKILL IN WRITING NARRATIVE AT MTS AL AMIN BRANTA PASISIR - . . Yuliarsih (Universitas Madura, 2019)
This research was intended to to find out the students’ skill in writing narrative at MTS Al Amin Branta Pasisir. In order to solve the problem, the researcher uses descriptive qualitative The number of sample in this research was 35 students which was taken from the eighth grade students. In this research, the researcher used writing test as the instrumentation of the research where the students were asked to write a narrative text based on the topics given to them. In this research, the researcher focus on five components of narrative text written by the students such as content, organization, vocabulary, language use and mechanic. To measure students’ skill, the researcher was helped by 3 raters where the result of the analysis showed that in the content of writing, students’ average score was 52,72 and it can be classified into the poor level. In the organization of writing, students’ average score was 50,47 and it can be classified into the poor level. In the vocabulary of writing, students’ average score was 51,31 and it can be classified into the poor level. In the language use, students’ average score was 52,80 and it can be classified into the poor level. In the mechanics, students’ average score was 52,70 and it can be classified into the poor level. From those results, the researcher found that the students’ average score in writing narrative text was 52 and it means their writing skill in narrative text can be categorized in the poor level.